Focused Cardiac Ultrasound Using a Pocket-Size Device in the Emergency Room - Mancuso,Frederico José Neves (2014)
Background:Cardiovascular urgencies are frequent reasons for seeking medical care. Prompt and accurate medical diagnosis is critical to reduce the morbidity and mortality of these conditions.Objective:To evaluate the use of a pocket-size echocardiography in addition to clinical history and physical exam in a tertiary medical emergency care.Methods:One hundred adult patients without known cardiac or lung diseases who sought emergency care with cardiac complaints were included. Patients with ischemic changes in the electrocardiography or fever were excluded. A focused echocardiography with GE Vscan equipment was performed after the initial evaluation in the emergency room. Cardiac chambers dimensions, left and right ventricular systolic function, intracardiac flows with color, pericardium, and aorta were evaluated.Results:The mean age was 61 ± 17 years old. The patient complaint was chest pain in 51 patients, dyspnea in 32 patients, arrhythmia to evaluate the left ventricular function in ten patients, hypotension/dizziness in five patients and edema in one patient. In 28 patients, the focused echocardiography allowed to confirm the initial diagnosis: 19 patients with heart failure, five with acute coronary syndrome, two with pulmonary embolism and two patients with cardiac tamponade. In 17 patients, the echocardiography changed the diagnosis: ten with suspicious of heart failure, two with pulmonary embolism suspicious, two with hypotension without cause, one suspicious of acute coronary syndrome, one of cardiac tamponade and one of aortic dissection.Conclusion:The focused echocardiography with pocket-size equipment in the emergency care may allow a prompt diagnosis and, consequently, an earlier initiation of the therapy.